Evaluation of Fournier’s gangrene severity index in the management of Fournier’s gangrene: a retrospective study - A., Shashirekha C.; T., Pramod; N., Nagaraj K.; Kumar, Harish; N., Rakesh (International Surgery Journal, 2016)
Background: Demonstration of the usefulness of Fournier’s gangrene severity index in the management of Fournier’s gangrene. Methods: A retrospective study of all the patients admitted to the hospital with Fournier’s gangrene was included in the study in the year 2012. Fournier’s gangrene was diagnosed by history and clinical examination. Details of the patients were obtained from the hospital register. FGSI was calculated using 9 parameters; heart rate, temperature, respiratory rate, sodium, potassium, serum creatinine, serum bicarbonate, leukocyte count and hematocrit. The score was graded 0±4. Results: The details of the patients were tabulated. The age of the patients ranged from 25 to 60 years (mean 44 years). All were male patients. The mean duration of disease before treatment was 7.5 days (ranged from 5 to 10 days). Three patients had diabetes and other patients did not have any risk factors. One among the diabetic was obese. Six patients had infection of scrotum and one patient had infection in with scrotal abscess needed I and D. Tissue and pus was sent for culture and sensitivity. Appropriate antibiotics were started covering aerobic and anaerobic organisms. Few patients required repeated debridement to minimize burden of infection. Antibiotics were changed according to culture sensitivity report. With repeated debridement and antibiotics, wound epithelized to surface. Secondary suturing was done as a corrective procedure to close the defect in 6 patients and split skin grafting was done in one patient as the defect was larger in size. FGSI was calculated in all patients. Five patients presented with necrotic patch, progressing rapidly needed necrosectomy initially and other patient presented treatment lasted for average of 45 days ranging from 38 to 55 days. All patients were cured with no mortality. Conclusions: Necrotizing fasciitis of the perineum and genitalia is a severe and rapidly progressive condition with considerable morbidity and mortality. Survival can be improved in a patient with Fournier’s gangrene by FGSI, aggressive surgical and medical management. FGSI is very useful in assessing the severity of the disease and high mortality associated with it. Continuous monitoring of all the parameters is essential for a good outcome, therefore reducing the high, mortality and morbidity of the condition.